2019
DOI: 10.1308/rcsann.2019.0098
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for leak, complications and mortality after ileocolic anastomosis: comparison of two anastomotic techniques

Abstract: Introduction There are no definitive data concerning the ideal configuration of ileocolic anastomosis. Aim of this study was to identify perioperative risk factors for anastomotic leak and for 60-day morbidity and mortality after ileocolic anastomoses (stapled vs handsewn). Materials and methods This is a STROBE-compliant study. Demographic and surgical data were gathered from patients with an ileocolic anastomosis performed between November 2010 and September 2016 at a tertiary hospital. Anastomoses were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
1
18
0
4
Order By: Relevance
“…However, other studies have found that diabetes was not a risk factor for anastomotic leakage [16,28]. [29]. These results were consistent with our underlying disease results, which suggested that the presence of underlying disease was associated with anastomotic leakage.…”
Section: Anastomotic Leakagesupporting
confidence: 92%
“…However, other studies have found that diabetes was not a risk factor for anastomotic leakage [16,28]. [29]. These results were consistent with our underlying disease results, which suggested that the presence of underlying disease was associated with anastomotic leakage.…”
Section: Anastomotic Leakagesupporting
confidence: 92%
“…The overall 60-day complication rate in that study was 27.3%. Male sex (31.3% complication rate vs 22.3% among female patients, P = 0.0200, OR: 1.7), diabetes (P = 0.0300, OR: 2.0), smoking habit (P = 0.0400, OR: 1.8), and perioperative transfusion (P < 0.0010, OR: 3.3 per liter) were independent risk factors for postoperative morbidity [29]. These results are consistent with our underlying disease results, which suggest that the presence of underlying disease is associated with anastomotic leakage.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, the overall 60-day complication rate in that study was 27.3%. The complication rate was 31.3% in male vs. 22.3% among female patients (P = 0.020, OR: 1.7), diabetes (P = 0.030, OR: 2.0), smoking habit (P = 0.040, OR: 1.8), and perioperative transfusion (P < 0.001, OR: 3.3 per liter) were independent risk factors for postoperative morbidity [26]. These results are consistent with our underlying disease results, which suggest that the presence of the underlying disease is associated with anastomotic leakage.…”
Section: Discussionmentioning
confidence: 90%